Novel Diphenylamine Analogs Induce Mesenchymal to Epithelial Transition in Triple Negative Breast Cancer - Bhatt, Akshita B.; Gupta, Mohit; Hoang, Van T.; Chakrabarty, Suravi; Wright, Thomas D.; Elliot, Steven; Chopra, Ishveen K.; Monlish, Darlene; Anna, Katie; Burow, Matthew E.; Cavanaugh, Jane E.; Flaherty, Patrick T. (Frontiers in Oncology, 2019)
Epithelial to mesenchymal transition (EMT) is a cellular program that converts non-motile epithelial cells into invasive mesenchymal cells. EMT is implicated in cancer metastasis, chemo-resistance, cancer progression, and generation of cancer stem cells (CSCs). Inducing mesenchymal to epithelial transition (MET), the reverse phenomenon of EMT, is proposed as a novel strategy to target triple negative and tamoxifen-resistant breast cancer. Triple negative breast cancer (TNBC) is characterized by the loss of hormone receptors, a highly invasive mesenchymal phenotype, and a lack of targeted therapy. Estrogen receptor-positive breast cancer can be targeted by tamoxifen, an ER antagonist. However, these cells undergo EMT over the course of treatment and develop resistance. Thus, there is an urgent need to develop therapeutic interventions to target these aggressive cancers. In this study, we examined the role of novel diphenylamine analogs in converting the mesenchymal phenotype of MDA-MB-231 TNBC cells to a lesser aggressive epithelial phenotype. Using analog-based drug design, a series of diphenylamine analogs were synthesized and they were initially evaluated for their effect on E-cadherin protein expression and changes incell morphology, which was quantified by measuring the spindle index (SI) value. Selected compound 1 from this series increases the expression of E-cadherin, a primary marker for epithelial cells, and decreases the mesenchymal markers SOX2, ZEB1, Snail, and vimentin. The increase in epithelial markers and the decrease in mesenchymal markers is consistent with a phenotypic switch from spindle-like morphology to cobblestone-like morphology. Furthermore, Compound 1 decreases spheroid viability, cell migration, and cell proliferation in triple negative BT-549 and tamoxifen-resistant MCF-7 breast cancer cells.